Reproductive health of men of industrial territories: risk factors, pre-nosologic diagnostics, prophylaxis - Serdyuk A.M.; Beletskaya E.N.; Stus V.P.; Onul N.M. (Medičnì Perspektivi)
Deterioration of the environment in the XX-XXI century under the influence of chemical, physical, radiological and other factors is not only and not just an ecological catastrophe of modern times, but a direct threat to the health and life of human society as a whole. Among the most important factors influencing people's health occupy chemical the leading place, because since 1957 more than 50 million chemical substances were synthesized, but only 15% of them have a toxicological evaluation, and 30% of the diseases in Europe are associated with chemical factor (ECHA-EXA). Chemical "pressing" determines a significant reduction in the reproduction of the population of Europe, and for Ukraine it means a large-scale depopulation, among possible reasons of which a significant role belongs to the deterioration of the reproductive capacity of population, men in particular, and this work is devoted to this problem. On the basis of profound analysis of literature data, complex ecologic-hygienic researches we identified markers of exposure, prognosticaly significant markers of impact for the early diagnostics of disorders of male generative system in conditions of low-dose impact of xenobiotics. We achieved convincing evidence of ecologically determined character of unogenital diseases and fertility decrease, we developed scientifically-justified principles of management of risk of development of ecologically-determined reproductive pathology in men.